PERHITUNGAN PAJAK PENGHASILAN (PPH) PASAL 21 MENGGUNAKAN TARIF EFEKTIF RATA-RATA (TER) ATAS GAJI PEGAWAI TETAP PADA CV BUMI TEMPOSOK - Muhammad Al-fareza; Hamdani; Melinda Wijaya (Universitas Lambung Mangkurat, 2025)
This study aims to analyze the application of Income Tax Article 21 (PPh 21) calculation using the Average Effective Rate (TER) method on the salaries of permanent employees at CV Bumi Temposok. The TER method was introduced by the Directorate General of Taxes to simplify the PPh 21 calculation process and improve tax administration efficiency. This research employs a descriptive quantitative approach, utilizing primary data obtained through observation and interviews, as well as secondary data from company documents and relevant literature. The results indicate that the application of the TER method at CV Bumi Temposok complies with the prevailing tax regulations, with tax calculations performed based on PTKP categories and established monthly effective rates. It was also found that several employees have zero tax status due to their gross income falling below the taxable threshold after accounting for allowable deductions. The implementation of TER has proven beneficial in saving calculation time, reducing potential errors, and ensuring tax compliance.